Outcome of Intertrochanteric Fractures in Elderly Patients treated with Dynamic Hip Screw. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of intertrochanteric fractures in elderly patients treated with Dynamic Hip Screw(DHS).Methods: This descriptive study was conducted in Orthopaedic Unit Pakistan Railway General Hospital Rawalpindi from 16th February 2016 and 16th February 2021.All elderly patients with stable intertrochanteric fractures(Evans type IA and Type IB) fulfilling the inclusion criteria were treated with DHS and functional outcome was evaluated at 6 months with Harris Hip Score(HHS) and results were graded as excellent(HHS score 90 to 100),good(HHS score 80 to 90), fair(HHS 70 to 80) and poor(HHS score